An experimental investigation on heat transfer characteristics of graphite-SiO2/water hybrid nanofluid flow in horizontal tube with various quad-channel twisted tape inserts - Dalkilic, Ahmet Selim; Turk, Osman Alperen; Mercan, Hatice; Nakkaew, Santiphap; Wongwises, Somchai (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Turbulent heat transfer characteristics of Graphite-SiO2/Water hybrid nanofluid flow in a horizontal smooth tube with and without quad-channel twisted tape (QCTT) inserts is investigated experimentally. The hybrid nanofluid is obtained using two different nanoparticles: Siliciumdioxid (60%) and Graphite (40%) with pure water as base fluid. Experiments are conducted for two different volume concentrations, 0.5% and 1%, respectively. The length of quad-channel twist tape inserts are between 0 and 42 cm with constant twist ratios of 5. The Reynolds number is varied from 3400 to 11,000. According to the results, Nusselt number of the case with hybrid nanofluid increased with increasing mass flow rate and volume concentration. Also, heat transfer coefficient increased with increasing length of twisted tape insert. Moreover, friction factor increases with increasing volume concentration for increasing Reynolds number whereas and friction factor increases with increasing the length of tape inserts. Pressure drop increases with increasing mass flow rate and increasing volume concentration. Finally, the regression equations are found to be well-matched with the experimental data within the deviation band of +/- 5% for Nusselt number and +/- 10% for friction factor, respectively.
Keywords: Hybrid nanofluid; Twisted tape insert; Friction factor; TRANSFER ENHANCEMENT; TURBULENT PIPE; PRESSURE-DROP; VISCOSITY; WATER; FLUIDS; AL2O3; TIO2; Thermodynamics; Mechanics